From Project to Strategic Vision: Taking the Lead in Research Data Management Support at the University of Sydney Library - Belinda Norman; Kate Valentine Stanton (International Journal of Digital Curation, 2014)
This paper explores three stories, each occurring a year apart, illustrating an evolution toward a strategic vision for Library leadership in supporting research data management at the University of Sydney. The three stories describe activities undertaken throughout the Seeding the Commons project and beyond, as the establishment of ongoing roles and responsibilities transition the Library from project partner to strategic leader in the delivery of research data management support. Each story exposes key ingredients that characterise research data management support: researcher engagement; partnerships; and the complementary roles of policy and practice.